Location of the major antigenic sites involved in rotavirus serotype-specific neutralization. - Dyall-Smith, M L (1986)
Antigenic sites on the rotavirus major outershell glycoprotein were identified by using mutant viruses selected for resistance to neutralizing (serotype-specific) monoclonal antibodies. The glycoprotein genes from these mutants were sequenced to determine the position and nature of the resultant amino acid substitutions in the protein. Three regions (A, B, and C) were identified (amino acids 87-96, 145-150, and 211-223, respectively), of which region C appears to be the most important. A mutation in region C caused a 10-fold increase in resistance to neutralization by polyclonal antiviral antiserum. The results of this study, together with other data, indicate that the three-dimensional folding of the native protein is such that regions A and C are in close proximity.